BACTERIAL SPECIES THAT CAUSE URINARY TRACT INFECTIONS IN PREGNANT WOMEN - Halala Mohammed Abdulla; Ibrahim Mohammed Saeed Hussein (European Science Publishing, 2024)
100 samples of urine were collected from pregnant women suffering from urinary tract infections of varying ages. The samples were planted on solid culture media (blood agar, MacConkey agar, and mannitol salt agar), where they incubated at a temperature of 37 Co for 24 hours. After culture, the samples were diagnosed. Direct method by microscope and indirect method using biochemical tests, and the diagnosis was confirmed using the Api 20 E system, where isolate 112 was isolated. The results of the study showed five types of bacteria causing urinary tract infections, which included Escherichia. coli with a percentage of 37%, Staphylococcus. aureus with a percentage of 25%. %, Klebsiella. pneumonia by 19%, Staphylococcus. epidermidis by 11% and pseudomonas. aeruginosa by 8%. Seven types of common antibiotics were used, and the results showed that all samples were 100% resistant to Trimethoprim, Erythromycin, Ampicillin and Tetracycline, and 78% resistant to Augmentin, and the results showed high sensitivity to Meropenem and Amikacin, with rates of 81 and 74, respectively.
Keywords: UTI, pregnant women, Bacterial species.